Transcriptomic analysis of purified human cortical microglia reveals age-associated changes - Galatro, Thais F; Holtman, Inge R; Lerario, Antonio M; Vainchtein, Ilia D; Brouwer, Nieske; Sola, Paula R; Veras, Mariana M; Pereira, Tulio F; Leite, Renata E P; Möller, Thomas; Wes, Paul D; Sogayar, Mari C; et al. (Nature neuroscience, 2017)
Microglia are the macrophages of the CNS, with innate neuroimmune function, and play important roles in tissue homeostasis, CNS development and neurodegeneration. Here human microglial gene expression profiles were generated. Human and mouse microglia were highly similar, except for aging-regulated genes, indicating that microglial aging differs between humans and mice. Microglia are essential for CNS homeostasis and innate neuroimmune function, and play important roles in neurodegeneration and brain aging. Here we present gene expression profiles of purified microglia isolated at autopsy from the parietal cortex of 39 human subjects with intact cognition. Overall, genes expressed by human microglia were similar to those in mouse, including established microglial genes CX3CR1 , P2RY12 and ITGAM ( CD11B ). However, a number of immune genes, not identified as part of the mouse microglial signature, were abundantly expressed in human microglia, including TLR , Fcγ and SIGLEC receptors, as well as TAL1 and IFI16 , regulators of proliferation and cell cycle. Age-associated changes in human microglia were enriched for genes involved in cell adhesion, axonal guidance, cell surface receptor expression and actin (dis)assembly. Limited overlap was observed in microglial genes regulated during aging between mice and humans, indicating that human and mouse microglia age differently.